Atherosclerotic plaque-targeted nanotherapeutics ameliorates atherogenesis by blocking macrophage-driven inflammation. (February 2022) - Yang, Hui; Liu, Chang; Wu, Yanjun; Yuan, Meng; Huang, Jiarun; Xia, Yuhan; Ling, Qinjie; Hoffmann, Peter R.; Huang, Zhi; Chen, Tianfeng
Highlights: MSeNP@CIP targets macrophages to treat atherosclerosis. MSeNP@CIP reduces aortic plaques by protecting ATP-binding cassette transporter against calpain proteolytic cleavage. MSeNP@CIP can reprogram macrophages to an M2 phenotype to exert anti-inflammatory effects. Graphical Abstract: ga1 Nanoparticles utilizing the D -mannose along with potent anti-inflammatory selenium and CIP (MSeNP@CIP) were synthesized as highly stabile, biocompatible therapeutic reagents targeting to the atherosclerotic lesion. MSeNP@CIP is capable of protecting the key regulators of cholesterol homeostasis ABCA1 against calpain by inhibiting the calpain activity, and ameliorated the foam cells formation substantially. It was also shown to upregulate the proportion of M2 phenotype macrophages thus exhibits anti-inflammatory effect. The present study provides a strategy for functionalization of nanomedicines using structure-optimized SeNP, and mechanistic insight for the precise treatment of atherosclerosis. Abstract: Atherosclerosis is a leading cause of death worldwide as characterized by the accumulation of lipid-overloaded macrophages exhibiting high expression of mannose receptors (MRs) in the arterial wall. Hyperactivation of the calpain proteolytic system has been reported to contribute to the progression of atherosclerosis through cleavage of ATP-binding cassette transporter A1 (ABCA1) and G1 (ABCG1) in macrophages. However, the efficiency and specificity of conventional calpain inhibitors are substantially limited, reducing their capacity to influence calpain mediated pathology. To address this issue, a translational nanosystem was developed using immune enhancing selenium in the form of D -mannose modified selenium nanoparticle (MSeNP) loaded with calpain inhibitory peptide (CIP) (MSeNP@CIP). The D -mannose modification enhanced accumulation of MSeNP@CIP in the atherosclerotic plaques by specifically binding to mannose receptors, thus reducing plaque formation via inhibition of calpain activity, leading to lower levels of atherosclerosis in apolipoprotein E-deficient (ApoE -/- ) mice. Moreover, by regulating the ratio of M1/M2 macrophages, MSeNP@CIP exhibits strong anti-inflammatory effects. Taken together, this study provides the framework for a targeted nanotherapy to mitigate atherogenesis.